Portable Stress Detection System for Autistic Children Using Fuzzy Logic - Melinda Melinda; Verdy Setiawan; Yunidar Yunidar; Gopal Sakarkar; Nurlida Basir (Department of Electrical Engineering at Universitas, 2024)
Non-Index Publication